The Position of Judges in the Indonesian Legal Idea - Moh. Mujibur Rohman; Elladdadi Mark; Kailie Maharjan (Yayasan Adra Karima Hubbi, 2023)
Background. Judges are state judicial officials authorized by law to adjudicate. The role of judges is very important in the judicial order in Indonesia. Purpose. As we know, the Indonesian government system adheres to the trias politica, namely the legislative body as the legislator in this case the DPR, the executive body, namely the government and its cabinet and finally the judicial body, namely the judiciary. Method. The writing of this article cannot be separated from the name of the research method, because in scientific writing the method is a necessity which is the perfect and effective condition of a research result Results. In addition to the government system, the Indonesian legal system is known to follow the European-Continental legal system where the law will be based on the law or what is known as